If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(n + -5) + 7(n + 1) = 0 Reorder the terms: -5(-5 + n) + 7(n + 1) = 0 (-5 * -5 + n * -5) + 7(n + 1) = 0 (25 + -5n) + 7(n + 1) = 0 Reorder the terms: 25 + -5n + 7(1 + n) = 0 25 + -5n + (1 * 7 + n * 7) = 0 25 + -5n + (7 + 7n) = 0 Reorder the terms: 25 + 7 + -5n + 7n = 0 Combine like terms: 25 + 7 = 32 32 + -5n + 7n = 0 Combine like terms: -5n + 7n = 2n 32 + 2n = 0 Solving 32 + 2n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 2n = 0 + -32 Combine like terms: 32 + -32 = 0 0 + 2n = 0 + -32 2n = 0 + -32 Combine like terms: 0 + -32 = -32 2n = -32 Divide each side by '2'. n = -16 Simplifying n = -16
| 4(x-3)+2(x-1)= | | -10(a+3)+6a= | | 7c-15-5c+42= | | 12-2c=2whatisc | | 6(n+3)+2n= | | -7(y-11)= | | -5+6c-5c= | | 5(1+3x)=125 | | -3n+8+8n= | | 40h+25k+35= | | -8c+c= | | -3a+11a= | | 305=0.15x+16y | | 9=2y-(2y-9) | | 2(x+15)=16 | | 305=0.15y+16x | | (7x+3y)-(2x-3y)= | | 10m-8m= | | -12-15x=3 | | 6(6+3x)=54 | | 24x+24y= | | -4(r-4s-9t)= | | 19.6t^2-14t+8=0 | | 45(-11-32)=c | | x-5=2(23.5)+12 | | -8(2t+6)=-112 | | 16=y+2 | | 2(4x-2)=7x | | 8(s-10)=-124 | | 16a^2-24a+1=0 | | -4+2x=-8+16 | | 4(10+7x)=152 |